Digitalisasi Sistem Pelayanan Dalam Meningkatkan Efisiensi Kerja Pegawai Dan Sistem Pelayanan Akademik Sebelum Pandemi Covid-19 Dan Masa Pandemi Covid-19 (Studi Kasus : Fakultas Tik Uinsi Dan Fakultas Saintek Umkt Samarinda) - Hendrita Lelen; I Ketut Gunawan; Anwar Alaydrus (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
The research objective was to find out the development of the application of digitalization of the academic service system before the Covid-19 Pandemic, namely at the beginning of the establishment of the Higher Education studied and during the Covid-19 Pandemic which had an impact on increasing employee work efficiency and academic services at the Faculty of SAINTEK UMKT Samarinda and FTIK UINSI Samarinda. This type of research is qualitative research with a case study approach. The subjects of this study were academic and IT staff at the Faculty of SAINTEK UMKT and FTIK UINSI Samarinda. The object of this research is a digitalization technology-based service and media system that is carried out online. The data is then obtained by several methods, namely; direct observation, interviews, and documentation. The data analysis technique used is; data collection, data reduction, data presentation and drawing conclusions. Based on the results of the research, it is known that the application of digitalization of the academic service system at the Faculty of SAINTEK UMKT and FTIK UINSI Samarinda before the Covid-19 Pandemic had begun to be implemented, namely since the beginning of the two tertiary institutions were inaugurated, but limited to several types of services. However, some efficiencies have been felt by employees, besides that, in improving services, the application of digitalization is able to create quality services that are efficient, responsive, transparent and effective.